Innovative Methods of Teaching Russian Language and Literature (Journal of Pedagogical Inventions and Practices, 2021)
The traditional education system lags somewhat behind the needs of society. The concept of modern education has determined the goal of the teacher's professional activity - to form students' ability to successfully socialize in society, actively adapt to the labor market. The consequence of this is the development of innovative technologies in teaching. Innovative methods are characterized by a new style of organizing educational and cognitive activities of students. Modern teachers admit that the technology of problem-based learning presents the maximum opportunities in the development of creative abilities, intellectual activity